Energy from coconut - Festin, Teodorico F.
The paper was written by Prof. Teodorico F. Festin, one of the few faculty members members from the College of Engineering to be confered the title of Professor Emeritus of the University of the Philippines. He served the University from 1951 until his retirement in 1989 in various positions, including the chairmanship of the Department of Chemical Engineering for 16 years. He was awarded the Dean Alfredo Juinio Lifetime Distinguished Achievement Award for 2007 in recognition of his various and valuable contribution to the field of Chemical Engineering. Prof. Festin obtained his Bachelor of Science degrees in Chemistry from the University of the Philippines and Chemical Engineering from the National University. He earned a Master of Science degree in Chemical Engineering from the University of California I Berkeley. He was also a Research Scientist at the prestigious Lawrence Radiation Laboratory in Berkeley. At the time this paper was written, Prof. Festin had been actively engaged in research projects involving agricultural residues. Among the studies he had done were : Pyrolysis of Rice Hull (BED-UNIDO, 1978), Coco Gas from Coir Dust (NSDB-NIST, 1974), Liquid Fuel Synthesis from Waste Products (NSDB-NIST, 1975), Hydrogenation of Solid Liquid Fuels I(NSDB-NIST, 1975). Among his other publications were "Energy from Coconut" in the Philipping Journal of Coconut Studies, in 1977 and "Pyrolysis of wastes", Philippine Engineering Journal, v. 3, no. 1, 1982.
Keywords: Coconut -- Products; Coconut energy